Promoting axonal regeneration following nerve surgery: a perspective on ultrasound treatment for nerve injuries - Bergmeister, Konstantin D.; Harhaus-Wähner, Leila (Neural regeneration research, 2018)
Neural Regen Res, Official publication of Publishing House of Neural Regeneration Research China Association of Rehabilitation Medicine,China
Gesehen am 27.06.2019